ROLE UNCERTAINTY AS A FACTOR AND CONDINTION FOR EFFECTIVE MANAGEMENT OF SOCIAL PROCESSES IN MODERN ORGANIZATIONS (Publishing House of the State University of Management, 2017)
The article presents the rationale of the relevance of learning management features role-playing uncertainty. Exposed the notion of uncertainty regarding the role demands and expectations. Considered the specificity of the role of uncertainty in the management of the organization. Highlighted four major roles are the basis of governance in organizations. Shows the possible combinations of roles of leader to exercise effective control. Revealed the effects of uncertainties for all roles of a Manager. The main factors influencing the activity of the leader in terms of role-playing uncertainty. However, ways to withdraw a role uncertainty of managers under conditions of modern organizations.